Efficient CRISPR-Cas9 Gene Disruption System in Edible-Medicinal Mushroom Cordyceps militaris - Chen, Bai-Xiong; Wei, Tao; Ye, Zhi-Wei; Yun, Fan; Kang, Lin-Zhi; Tang, Hong-Biao; Guo, Li-Qiong; Lin, Jun-Fang (Frontiers in Microbiology, 2018)
Cordyceps militaris is a well-known edible medicinal mushroom in East Asia that contains abundant and diverse bioactive compounds. Since traditional genome editing systems in C. militaris were inefficient and complicated, here, we show that the codon-optimized cas9, which was used with the newly reported promoter Pcmlsm3 and terminator Tcmura3, was expressed. Furthermore, with the help of the negative selection marker ura3, a CRISPR-Cas9 system that included the Cas9 DNA endonuclease, RNA presynthesized in vitro and a single-strand DNA template efficiently generated site-specific deletion and insertion. This is the first report of a CRISPR-Cas9 system in C. militaris, and it could accelerate the genome reconstruction of C. militaris to meet the need for rapid development in the fungi industry.